Volatile essential oil constituents of Alpinia smithiae (Zingiberaceae) - Joseph, Roy (2001)
The composition of leaf and rhizome essential oils of Alpinia smithiae that grow wild in the Western Ghats of Kerala (South India) was analysed by gas chromatography. The major components were β-caryophyllene, sabinene, myrcene and 1,8-cineole in both samples, but variation in the yield of oil as well as the major components between the two plant parts was observed.